The Ferroptosis-NLRP1 Inflammasome: The Vicious Cycle of an Adverse Pregnancy - Meihe, Li; Shan, Gao; Minchao, Kang; Xiaoling, Wu; Peng, An; Xili, Wu; Jin, Zheng; Huimin, Dang (Frontiers in Cell and Developmental Biology, 2021)
One of the hallmarks of placental dysfunction is the increase of oxidative stress. This process, along with the overexpression of the inflammasome, creates a downward spiral that can lead to a series of severe pregnancy complications. Ferroptosis is a form of iron-mediated cell death involving the accumulation of reactive oxygen species, lipid peroxides. In this study, the rats’ model of oxidative stress abortion was established, and hydrogen peroxide (H2O2) was used to establish a cellular model of placental oxidative stress. RNAi, western blot, and immunofluorescence were used to evaluate the expression of specific markers of ferroptosis and the expression of the inflammasome in placental trophoblast cells. We observed excessive levels of ferroptosis and inflammasome activation in both rats’ model and placental trophoblast cell model of oxidative stress. When the NLRP1 inflammasome was silenced, the expression levels of GSH and Glutathione peroxidase 4 (GPX4) were increased, while the expression levels of transferrin receptor 1 (TFR1), acyl-CoA synthetase long-chain family member 4 (ACSL4), Superoxide dismutase (SOD), and Malondialdehyde (MDA) were decreased. However, when an NLRP1 activator was applied, we observed the opposite phenomenon. We further explored the mechanisms underlying the actions of ferroptosis to inflammasomes. The expression levels of NLRP1, NLRP3, IL-1β, and caspase-1 were positively correlated with the ferroptosis following the application of ferroptosis inhibitor(ferrostatin-1) and ferroptosis activator (erastin). The existence of ferroptosis was demonstrated in the oxidative stress model of placental trophoblast cells; the results also indicate ferroptosis is linked with the expression of NLRP1 inflammasome. These findings may provide a valuable therapeutic target for the pathogenesis of pregnancy-related diseases.